Daniel Chirot (comp.). The Crisis of Leninism and the Decline of the Left, the Revolutions of 1989. Seattle y Londres: University of Washington Press, 1991, 245 pp. - Connelly, Marisela (Estudios de Asia y África, 1993)
-